Identifying the best metal–organic frameworks and unravelling different mechanisms for the separation of pentane isomers. Issue 3 (16th April 2019) - Qiao, Zhiwei; Cheetham, Anthony K.; Jiang, Jianwen
Abstract : Six different mechanisms are unraveled for the shape and inverse-shape selective adsorption of C5 isomers in metal–organic frameworks by high-throughput computational screening. Abstract : The development of energy-efficient technologies for the separation of alkane isomers is important in the chemical and petrochemical industries. We report a high-throughput computational screening study of metal–organic frameworks (MOFs) for the selective adsorption of three pentane isomers: n -pentane, 2-methylbutane and 2, 2-dimethylpropane. The best candidates are identified and have adsorption selectivities several orders of magnitude higher than the best MOF (VICDOC) reported in the literature. For the first time, six subtly different separation mechanisms are unravelled from the complex interplay between pore size and shape in the MOFs.